Efeito dos óleos essenciais de Thymus vulgaris, Origanum vulgare e dos terpenos timol e carvacrol, sobre adultos e massas ovígeras de Pseudosuccinea columella - Ito, Mitsue (2021)
Fasciolosis is a disease with worldwide distribution that can lead to great economic losses in ruminant breeding and has aquatic molluscs as an intermediate host, with Pseudosucinea columella being one of the most frequent species. Synthetic molluscicides are indicated for the control of molluscs, however, they are toxic to several species of plants and animals, being harmful to the environment. Due to the need to search for new natural substances, less harmful to the environment and that can act in the control of molluscs, the aim of the study was to evaluate the effect of essential oils from Thymus vulgaris, Origanum vulgare and terpenes thymol and carvacrol, on adults and ovigerous masses of P. columella. The oils of T. vulgaris, O. vulgare and the major ones, thymol and carvacrol, were diluted in concentrations of 10, 20, 40, 60, 80 and 100 ppm, as a positive control using copper sulfate (CuSo4) and as negative control, drinking water (H2O) and 1% Dimethylsulfoxide (DMSO) (solutions diluent) were used. The molluscs were divided into groups of 10 specimens for each solution, the different test solutions were exposed for a period of 24 hours and evaluated during this period at times of 30 minutes, two, six, 12 and 24 hours. The same methodology was used with the ovigerous masses, however, the masses were exposed to substances for 24 hours, went through the washing process and were evaluated for 18 days after exposure. During the biological study of adult molluscs, it was observed that essential oils of oregano at concentrations of 60, 80 and 100 ppm and thyme at a concentration of 100 ppm led to the death of 100% of them and were within the standards established by the World Health Organization for a complex mixture of substances. Essential oils and major components proved to be effective in inhibiting the growth and hatching of doughs. Only the masses exposed to the majority of thymol, at concentrations of 10, 20 and 40 ppm, hatched. Regarding histology, it was possible to observe vacuolization and fragmentation in the tissues of the digestive gland, ovotestis and mantle in molluscs treated with essential oils and major components. It was also noted in histology, areas of autolysis in molluscs treated with thymol at a concentration of 80 ppm. Scanning Electron Microscopy (SEM) showed tissue changes in the digestive gland and mantle at 100 ppm concentrations of essential oils and their major components. Thus, it can be concluded that the essential oils of O. vulgare and T. vulgaris behaved as molluscicide substances in P. columella. In addition, inhibitory effects were noted on the growth and hatching of ovigerous masses treated with the major components and essential oils studied.